До питання про законодавче закріплення поняття сім'ї - Ватрас, В.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
In the article the problems of legal definition of family, their differences from the prevailing legal science in the sociological understanding of the family.Through a creative synthesis of the views of scientists, analyzing legislation and the allocation of key properties, proposed his own definition of the family. The author proposes to enshrine in legislation his own definition of family, by adopting the new wording of art. 3 of the Family Code. Исследованы вопросы юридического определения семьи, его отличия от распространенного в юридической науке социологического понимания семьи. Путем творческого обобщения взглядов ученых, анализа законодательства и выделения ключевых свойств предложено собственное определение семьи. Автор предлагает закрепить на законодательном уровне это определение семьи путём принятия новой редакции ст. 3 Семейного кодекса Украины.